Similaridade do sítio de vocalização em uma comunidade de anfíbios anuros na região noroeste do Estado de São Paulo, Brasil - Rossa-Feres, Denise de C. [UNESP]; Jim, Jorge [UNESP] (Sociedade Brasileira de Zoologia, 2001)
The breadth and overlap of male call site were determined for 15 anuran species from a temporary pond in Northwestern São Paulo State, Brazil. Four measurements were made at the point of capture of each calling male and the frequency of mating call was determined. There was a high overlap along each variable of call site, but less than 28% of possible species pairs presented high overlap for all variables. Taxonomically related species pairs calling from grass presented spatial and acoustic segregation, while those calling from the graund presented only acoustic segregation. The similarity of call site seems to be not only related to the taxonomic relationships but also with the body size and spatial heterageneity.
Similarity of call site in anuran community in Northwestern São Paulo State, Brazil (Amphibia, Anura)
Keywords: Anura; vocalization site; microhabitat; Community ecology; similarity at call site